О единстве и различиях в пеньковской культуре - Приходнюк, О.М. (Материалы по археологии, истории и этнографии Таврии, 1998)
The results of lasting investigation of Penkovo antiquities spread on the boundaries of forest-steppe and steppe from the Severny (northern) Donets and the Lower Danube region are given in this article. The advanced stage is divided into two chronological phases dated back to the 5th and 6th-7th centuries A.D. The early Penkovo monuments of the 4th century A.D, of the Roitsch-Bogorodichnoe type are known only on the left bank of the Dnieper. On the materials of the second phase of the advanced stage, in unique Penkovo massif, we single out 4 main variants of Penkovo culture with its peculiarities, generated by the influence of the contacting archaeological massifs and some others factors. They are the regions of the bank of the Dnieper, the region between the Dnieper and Dnester, the region of the Dnieper Nadporozhie and Orel region, the region between the Dniester and the Prut river. Besides, in Romanian Moldova there is an infiltration zone, where the features of Penkovo, Prague and Geto-Daci features are traced on one and same monuments. Penkovo antiquities on all stages of their existance and on local territories are marked by the common distinguishing material, i.e. they have all features of an independent archaeological culture.